How to do better on your next closure plan - Hill, K.; Goslin, L.; Beale, G. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
A closure plan is required as part of the initial mine permitting process in most regulatory jurisdictions. Most initial closure plans, however, are based on limited data and inadequate site understanding. Caution is therefore required to avoid over-commitments that may lead to unrealistic closure cost estimates and the implementation of strategies which may later need to be undone once the knowledge base for the site improves. Data collection and technical studies should be initiated as early as possible in the project lifecycle in order to understand the risks, opportunities and requirements for closure. This allows for the integration of closure considerations into the mine plan, and makes it easier and more cost-effective to achieve final closure objectives. This paper presents three case studies that exemplify the need for high-quality data early in the closure planning process: An open pit mine in North America provides a good example of interactive closure planning, with geotechnical, hydrogeological and geochemical goals collectively considered. Based on detailed technical studies and monitoring data, the pit was backfilled with reactive waste material and rapidly filled using operational dewatering wells to quickly submerge the reactive backfill. A chemically stable pit lake was established that meets most regulated water quality standards. At a mine site in Africa the closure strategy for a legacy tailings storage facility was significantly refined on the basis of results from geochemical testwork and hydrogeological investigations. It was found that the hazard inherent to the facility was low and that it could be rehabilitated in situ, with significant cost savings. At a prospective mine site in South Africa integrated technical studies have allowed for the development of a progressive closure strategy involving backfilling of open pits with tailings during the course of mine operations. This allows for a reduction in post-closure rehabilitation costs as these are largely absorbed during operations.